Farmland alongside Roches Gulch - Branch Cultural Historical Association (2010)
Like that of Englishs Gulch, the land around Roches Gulch was cleared for farming in the 1800s. Patrick Roche (1803 1892) obtained the land as a wedding gift when he married Nellie English. The early Roches temporarily moved to the Gulch to escape a virus that was circulating around Branch.